A study on the impact of digital infrastructure development on the health of low-income rural residents: based on panel data from 2010 to 2022 - Qian Wang; Zhen Ning; Meichun Tan (Frontiers in Public Health)
The health status of low-income rural residents is intricately linked to social equity and justice and the realization of the goal of common prosperity. Based on the CFPS data from 2010 to 2020 and the list of “Broadband China” demonstration cities, this paper employs a multi-period Difference-in-Differences (DID) approach to empirically analyze the impact of digital infrastructure construction on the health of low-income rural residents and its mechanism. The results indicate that: (1) Digital infrastructure construction had a significant positive impact on the health of rural low-income residents. After adjusting the sample period, changing the policy implementation time point, excluding other policy interference, and Propensity Score Matching-Difference-in-Differences (PSM-DID), the model was still robust. (2) The mechanism test found that digital infrastructure would improves the health of rural low-income residents through three mechanisms: the adoption of new agricultural technology, land transfer, and leisure time. (3) In terms of heterogeneity analysis, based on region type, education level, marital status and public supporting system, digital infrastructure construction can enhance the health status of low-income rural residents in the western region, those with low education level, married people and those with more public supporting system. This study suggests the continued promotion of the construction of digital infrastructure, with a focus on the construction level of the western and western regions, narrow the “digital divide” between different groups, and improve public supporting facilities in backward rural areas, so as to further enhance the health status of low-income groups.